Water use efficiency and consumption in different Brazilian genotypes of Jatropha curcas L. subjected to soil water deficit. (April 2015) - de Santana, Tessio A.; Oliveira, Priscila S.; Silva, Leandro D.; Laviola, Bruno G.; F. de Almeida, Alex-Alan; Gomes, Fábio P.
Abstract: In order to quantify the water use efficiency and water consumption during the early growth of Jatropha curcas L., three genotypes were grown in pots under greenhouse conditions, and subjected to two watering regimes: irrigated (substrate matric potential ( Ψ m ) of −9.8 to −7.4 kPa) and water deficit ( Ψ m  = −98.6 to −33.5 kPa). Independent of watering regime, the genotypes did not differ on the variables analyzed. Despite the reduction of substrate water content in water deficit treatment, no significant decrease (p < 0.05) of leaf water potential ( Ψ w ) was observed, which suggests some water redistribution from the succulent stems of J. curcas . The values of net photosynthetic rate ( A ), stomatal conductance ( gs ), and transpiration ( E ) were reduced to 80, 90 and 85%, respectively, as compared to control plants. Moreover, drought led to 78% reduction in hydraulic conductance ( K L ). At the end of the experiment, the average water consumption in water deficit plants was 27% lower than in control plants. Drought-induced decrease in biomass production led to reduction of water use efficiency of biomass (WUEBiomass ). However, due to the more significant effect on gs and E than A at 66 DAIT, intrinsic ( A/gs ) and instantaneous efficiency ( A/E ), water use increased 50% and 27%, respectively. The results showed that there was no intergenotypic variation for the traits evaluated, and that the reduction of water availability in the substrate proved to be an effective technique in the increase of photosynthetic efficiency of water use in plants of J. curcas, reducing water consumption in this species. Highlights: Three genotypes of J. curcas were grown under well-watered or drought conditions. Drought-induced changes in leaf gas exchange, growth and water use were reported. Low intergenotypic variation and increased photosynthetic WUE were identified.